1999
DOI: 10.1136/bjo.83.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Reflective meniscometry: a non-invasive method to measure tear meniscus curvature

Abstract: Aims-To devise a method to measure tear meniscus curvature by a non-invasive specular technique. Methods-A photographic system was devised. The system consisted of a camera and an illuminated target with a series of black and white stripes oriented parallel to the axis of the lower tear meniscus. The target was mounted on a flash gun close to the objective of a Brown macrocamera and calibrated using a graduated series of glass capillaries of known diameter, ground down to expose the inner wall. It was then app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 17 publications
1
62
0
3
Order By: Relevance
“…Several methods are available to assess tear quantity, including slit-lamp evaluation with a graticule scale, optical pachymetry, video meniscometery and optical coherence tomography (OCT), which have all been used to quantify the tear meniscus (Mainstone et al 1996;Yokoi et al 1999;Doughty et al 2001;Johnson & Murphy 2005;Savini et al 2006;Wang et al 2006). Several non-invasive tear break-up time tests have been developed to evaluate tear film stability.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are available to assess tear quantity, including slit-lamp evaluation with a graticule scale, optical pachymetry, video meniscometery and optical coherence tomography (OCT), which have all been used to quantify the tear meniscus (Mainstone et al 1996;Yokoi et al 1999;Doughty et al 2001;Johnson & Murphy 2005;Savini et al 2006;Wang et al 2006). Several non-invasive tear break-up time tests have been developed to evaluate tear film stability.…”
Section: Introductionmentioning
confidence: 99%
“…13 On the ocular surface of healthy subjects evaluated by meniscometry, an AT reportedly increased fluid volume for~2 min after instillation, and sodium hyaluronate increased the fluid volume for 5 min. 18 The fluid volume at 15 min after instillation of DQS was increased in the SS patients with dry eye and decreased lacrimal gland function. This longer mode of action may contribute to protect the ocular surface from the desiccation and ameliorate the epithelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although the ΔTMR value is appropriate for evaluation of an increase in aqueous tear volume over time on the same ocular surface, it is impossible to compare the change in radius values of different eyes. 18 Nonetheless, it is very interesting that the increase in aqueous tear volume after instillation of DQS was similar in healthy subjects and SS patients with decreased lacrimal gland function. Moreover, the results of this present study showed that there was no significant correlation between the ΔTMR and Schirmer 1 test values, which reflect reflex tear secretion from the lacrimal glands, and no significant difference from those in the AT-treated eyes, even in patients with ocular irritation considered to be the trigger of reflex tear secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…К ним относят: определение времени разрыва слез-ной пленки (ВРСП), определение симптоматического времени разрыва слезной пленки (СВРСП), компрес-сионную пробу, которая предполагает выдавливание секрета из устьев протоков мейбомиевых желез при их компрессии [5]. Кроме того, дефицит липидов, возник-ший как следствие ДМЖ, приводит к повышенному ис-парению водной фазы слезы, поэтому для определения тяжести процесса проводят тест Ширмера и биометрию слезного мениска [6,7].…”
unclassified